2001
DOI: 10.1054/bjoc.2000.1626
|View full text |Cite
|
Sign up to set email alerts
|

A probability model for predicting BRCA1 and BRCA2 mutations in breast and breast-ovarian cancer families

Abstract: Mutations in the two breast-ovarian cancer susceptibility genes, BRCA1 and BRCA2, account for a varying fraction of breast cancer families in different populations (Szabo and King, 1997). Both BRCA1 and BRCA2 mutations are scattered throughout the large coding regions of the genes (Breast Cancer Information Core). In admixed populations, most mutations appear uniquely in single families only, making the mutation screening laborious and expensive. Furthermore, there is also evidence of other predisposing genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
77
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(78 citation statements)
references
References 23 publications
0
77
1
Order By: Relevance
“…Of the altogether 1182 invasive breast cancers, 36 tumours were from BRCA1 and 40 tumours from BRCA2 mutation positive families; 740 tumours were from other familial breast cancer patients and 366 from sporadic patients. BRCA1/2 mutations had been excluded for all the 428 cases with strong family history of cancer (three or more, first-or second-degree relatives with breast or ovarian cancer), as well as, for 154 of the 312 cases from families with two affected first-degree relatives (BRCA1/2 mutation screening described in Vehmanen et al, 1997;Vahteristo et al, 2001Vahteristo et al, , 2002. The study was performed with informed consents from the patients as well as permissions from the Ethics Committee (E8) of the Helsinki University Central Hospital and from the Ministry of Social Affairs and Health in Finland.…”
Section: Resultsmentioning
confidence: 99%
“…Of the altogether 1182 invasive breast cancers, 36 tumours were from BRCA1 and 40 tumours from BRCA2 mutation positive families; 740 tumours were from other familial breast cancer patients and 366 from sporadic patients. BRCA1/2 mutations had been excluded for all the 428 cases with strong family history of cancer (three or more, first-or second-degree relatives with breast or ovarian cancer), as well as, for 154 of the 312 cases from families with two affected first-degree relatives (BRCA1/2 mutation screening described in Vehmanen et al, 1997;Vahteristo et al, 2001Vahteristo et al, , 2002. The study was performed with informed consents from the patients as well as permissions from the Ethics Committee (E8) of the Helsinki University Central Hospital and from the Ministry of Social Affairs and Health in Finland.…”
Section: Resultsmentioning
confidence: 99%
“…The first series included 888 unselected (described in detail in Syrjakoski et al 17 and Kilpivaara et al 18 ) and 946 familial 16 breast cancer patients collected at the Helsinki University Central Hospital in Southern Finland. BRCA1 and BRCA2 mutations have been excluded in all the 403 patients with a strong family history of cancer (three or more first-or second-degree relatives with breast or ovarian cancer in the family, including the proband) as well as in 291 cases with one affected relative as previously described 2,15,17 (also unpublished data). DNA from altogether 736 healthy female subjects collected at the same geographical region of Southern Finland was studied as healthy population controls.…”
Section: Methodsmentioning
confidence: 99%
“…Germline mutations in these genes are found in the majority of families (75 -80%) with both early-onset breast cancer and ovarian cancer, but in a considerably lower fraction of families with site-specific female breast cancer (no ovarian cancer or male breast cancer). 1,2 Recently, the CHEK2 1100delC and Ile157Thr have been identified as new low-risk breast cancer susceptibility alleles. 3 -5 It has been suggested that a substantial proportion of the remaining familial aggregation of breast cancer might be attributed to several such low penetrance alleles that act multiplicatively, and thereby form a polygenic basis for breast cancer predisposition.…”
Section: Introductionmentioning
confidence: 99%
“…The major known high-penetrance predisposition genes BRCA1 and BRCA2 account for a large majority of families with multiple cases of early-onset breast cancer and ovarian cancer, but only a small fraction of familial breast cancer without these characteristics. 14,15 Genetic linkage studies have suggested breast cancer loci on chromosomes 2q32, 6q25, 8p21, and 13q22. 16 -19 So far, the putative susceptibility genes in these regions have not been identified.…”
Section: Introductionmentioning
confidence: 99%